Theoretical and Methodological Approaches to Definition of Concept of Constitutional Right for Strike - Kolomoiets, Yuliia O.; Коломоєць, Юлія О.; Bonyak, Valentyna O.; Боняк, Валентина О.; Khoroshilova, Irina O.; Хорошілова, Ірина О. (University of Craiova, Romania, 2018)
The article deals with existing theoretical and methodological approaches to the definition of the concept ‘constitutional right to strike’. On the basis of their analysis the authors have reasoned that the constitutional right to strike is a socially determined, determined by the objective law norms the measure of possible (permissible) behavior of able-bodied subjects as an authorized party to the constitutional-legal relations, consisting in the temporary collective voluntary termination of work and provided to protect their own and general socio-economic rights and interests of the labor collective, provided by the behavior of the obliged party and guaranteed by the state. They have proved that the essence of the strike is the ability of each employee to protect both their own and collective social and economic rights and interests. The right to strike is a social regulator of conflict situations when other possibilities for their solution are exhausted. The authors have determined that this right is considered to be mixed – is being realized both individually and collectively. У статті розглядаються існуючі теоретичні та методологічні підходи до визначення поняття «конституційне право на страйк». На основі свого аналізу автори аргументували, що конституційне право на страйк є соціально обумовленим, визначеним об'єктивними правовими нормами мірою можливої (допустимої) поведінки працездатних суб'єктів як уповноваженої сторони конституційно-правових відносин , що полягає у тимчасовому колективному добровільному припиненні роботи та забезпечується для захисту власних та загальних соціально-економічних прав та інтересів трудового колективу, забезпечується поведінкою зобов'язаної сторони та гарантується державою. Вони довели, що суть страйку полягає в здатності кожного працівника захищати як власні, так і колективні соціальні та економічні права та інтереси. Право на страйк - це соціальний регулятор конфліктних ситуацій, коли інші можливості для їх вирішення вичерпані. Автори визначили, що це право вважається змішаним - реалізується як індивідуально, так і колективно.
Теоретичні та методологічні підходи до визначення поняття конституційне право на страйк
Keywords: citizens' right to association; право громадян на об'єднання; constitutional right to strike; конституційне право на страйк; strike; страйк; subjective right; суб'єктивне право